How Is The Tourism Informal Sector Resilience In Bali? - Ni Made Ary Widiastini; Trianasari; Putu Indah Rahmawati (Prospek: Jurnal Manajemen dan Bisnis, 2022)
This paper aimed to identify and explain how informal sector workers in tourism were trying to maintain their business viability in difficult times. The prolonged pandemic not only had an impact on declining sales due to a decrease in the number of tourist arrivals but also high competition presented as a result of the emergence of similar traders who were occupied by those affected by layoffs. Research using a qualitative approach, involving actors in the informal tourism sector as respondents, both producers, distributors, and traders, found that there was a lot of product development sold in tourist destinations caused by the emergence of local people as tourists. The dominance of local and domestic communities as tourists in tourist destinations demands that economic actors selling products at tourist attractions and their surroundings in Bali always understand the development of consumer needs and desires, especially domestic tourists.